Alligator pepper/Grain of Paradise (Aframomum melegueta) modulates Angiotensin-I converting enzyme activity, lipid profile and oxidative imbalances in a rat model of hypercholesterolemia. Issue 3 (September 2016) - Adefegha, Stephen A.; Oboh, Ganiyu; Adefegha, Omowunmi M.; Henle, Thomas
Abstract: Alligator pepper [ Aframomum melegueta Roscoe K. (Zingiberaceae)] seeds have been reportedly used in folkloric medicine in the management of hypercholesterolemia and hypertension with limited scientific basis for their action. This study was conducted to characterize the amino acids in Alligator pepper seeds (APS), assess their effects on lipid profile and enzyme linked to blood pressure regulation in hypercholesterolemic rat (rats fed 2% cholesterol diet) model. Free and total amino acids of APS were extracted and their various constituents were analyzed using the amino acid analyzer and ultra-performance liquid chromatography. The effect of dietary inclusion of APS (2–4%) on the lipid profile, angiotensin I-enzyme (ACE) activity and antioxidant status in hypercholesterolemic rats (HCR) for 30 days was assessed. The results suggest that APS may modulate blood lipid profile, ameliorate blood pressure, attenuate hepatotoxicity and exert antihypercholesterolemic effect. γ − amino butyric acid (GABA), tyrosine, phenylalanine and tryptophan that were subsequently detected in APS. The observed salutary effects of APS may be attributed to the synergistic or/and additive actions of the amino acids present with other antioxidant phytoconstituents. These findings may therefore provide pharmacological basis for APS use in the treatment of hypercholesterolemia, hyperlipidemia and hypertension.